Nutritional Content, Subchronic Toxicity, and Antidysmenorrhea Activity of Instant Herbal Medicine Mixture of Red Ginger and White Ginger - Dewi, Vonny Khresna; Kirana, Rita; Rizki, Muhammad Ikhwan (Medical Laboratory Technology Journal, 2025)
Dysmenorrhea is menstrual pain that occurs in 69.8% of women. Ginger (Zingiber officinale) contains various secondary metabolites with anti-inflammatory properties. This study aims to determine its characteristics, including nutritional value and stability, product safety through toxicity testing, and product efficacy. The research stages include research ethics testing and the production of instant powder from a mixture of red and white ginger. Nutritional content analysis included total fat, saturated fat, protein, and carbohydrates. Physical and chemical stability testing was carried out for three months. Subchronic toxicity testing used Wistar rats for 28 days by drawing blood before and after treatment, accompanied by liver delivery. Blood samples were analyzed for SGPT and SGOT levels. The test was conducted on 10 women aged 18-20, divided into two groups. The treatment group was given 20 grams of instant ginger in the morning and evening for 10 days, and compared with the control group without treatment. Pain was measured using a Visual Analog Scale (VAS) before and after the study. The study showed that instant ginger herbal medicine contained 0.83% total fat, 0.17% saturated fat, 3.73% total protein, and 35.42% total carbohydrates. The stability test results showed no changes in the physical and chemical parameters of the test. The results of the subchronic toxicity test showed that the body weight of mice, liver weight, SGOT levels, and SGPT levels of mice were normal. The activity test showed a decrease in pain from before to after administration of instant ginger, with an average VAS value of 7.8 to 4.2. This study concluded that instant ginger, a mixture of red and white ginger, has good nutritional content, is physically and chemically stable, is non-toxic, and is effective in reducing dysmenorrhea.